Dumbbell shaped inline Mach-Zehnder interferometer for glucose detection - Lokman, A.; Arof, Hamzah; Harun, Sulaiman Wadi (Elsevier Sci Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1gb, Oxon, England, 2015)
A simple inline Mach Zehnder Interferometer (MZI) with a dumbbell-shaped structure is developed for measuring glucose concentration in distilled water. The MZI is fabricated using an arcing function of a fusion splicer. The sensor consists of two bulges separated by a tapered waist. The MZI generates a good reflected interference spectrum where the dip wavelength is red-shifted with the increase of glucose concentration. This is due to the increase of the surrounding refractive index, which reduces the phase difference between the core and cladding modes. As the glucose concentration increases from 0 to 12, the dip wavelength increases from 1554.419 to 1554.939 nm in a quadratic manner with the coefficient of determination of 0.9818. It is also found that the sensor has a sensitivity of 0.04 nm/ with a linearity of 96.7. The limit of detection is 4.5. This preliminary result shows that the proposed probe can be used as a sensor to detect glucose concentration in distilled water. (C) 2014 Elsevier Ltd. All rights reserved.